1997
DOI: 10.1111/j.1095-8339.1997.tb02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of endangered Cuban cycad Microcycas calocoma (Miq.) A.DC.

Abstract: Observations indicate that natural regeneration in the field of the cycad Microcycas calocoma (Miq.) A.DC. is extremely low, and has been so since early this century. It appears that populations of its insect pollinator are practically extinct, but some pollinator activity appears to be present in the largest population of Microcycas. Recommendations for identification and captive breeding of die pollinator are suggested as a complementary conservation strategy to a Microcycas propagation programme already est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…The species is entomophilous which accords with that reported for other Neotropical cycads (Tang 1987;Norstog and Fawcett 1989;Vovides 1991;Vovides et al 1997b). …”
Section: Introductionsupporting
confidence: 88%
“…The species is entomophilous which accords with that reported for other Neotropical cycads (Tang 1987;Norstog and Fawcett 1989;Vovides 1991;Vovides et al 1997b). …”
Section: Introductionsupporting
confidence: 88%
“…A disruption of such a relationship has been observed: the pollinating beetle (still unidentified) of an endangered Cuban cycad became extinct and the remaining, cultivated individuals of this species now only produce seeds after artificial pollination, a common technique in botanical gardens (Vovides et al 1997).…”
Section: Sexmentioning
confidence: 99%
“…Insects appear to be the pollination agent in most cycad species (Norstog, 1987;Ornduff, 1991;Vovides, 1991;Vovides et al, 1997), yet no pollinators were observed for C. seemannii and it appears that the species is wind-pollinated. Even if its ancestor had been insect pollinated, the pollinator may not have had the ability to cross the ocean with the cycad seeds.…”
Section: Discussionmentioning
confidence: 99%